The Open Access Mystery - Sundsbø, Katrine (Septentrio Conference Series, 2020)
In this exciting Open Access themed mystery you’ll join a conference as one of eight characters who may or may not know each other from previous events and/or collaborations. During the conference disaster will strike, and it’s up to you to figure out who’s behind what turns out to be a global lockdown of all research. Will it be the Professor who relies on the h-index? The early career researcher with imposter syndrome? The problem solver who works in publishing? Or perhaps it’s the paranoid researcher who thinks you’ve stolen her ideas? Pay attention, not all is as it seems…Sign up is required for this activity! You’ll be assigned a character before joining the session and you will receive some background information about your character at this point. Dressing up as your interpretation of the character is highly encouraged.
Keywords: Open Access; Games; Gamification; Scholarly Communications; Mystery